Interventions for disruptive behaviors reducing problems and building skills - Fabiano, Gregory A. (New York The Guilford Press, 2016)
"Children and adolescents with disruptive behavior disorders struggle both in and outside the classroom. This book gives school practitioners vital tools for supporting students' positive behavior as well as their academic and social success. Chapters review effective behavioral interventions at the whole-class, targeted, and individual levels; parent training programs; and strategies for building adaptive skills. Core evidence-based techniques are illustrated with vivid, concrete examples. Ways to integrate the strategies into a school's multi-tiered model of prevention and intervention are discussed. In a large-size format with lay-flat binding for easy photocopying, the book includes 14 reproducible forms and handouts. Purchasers get access to a Web page where they can download and print the reproducible materials"--Provided by publisher.
"The purpose of this book is to provide an overview of the identification, contextual influences, and interventions that are appropriate for youth with disruptive behavior. Many sources exist to support these aims. This book serves to extend the literature by including resources, assessments, and strategies that may be useful for school practitioners across home, school, and community settings"--Provided by publisher.
Machine generated contents note: 1. Introduction -- 2. A function based approach to intervention -- 3. Overview of assessment for informing intervention -- 4. Parent training interventions -- 5. School interventions -- 6. Training interventions in adaptive skills -- 7. Maintenance and generalization of intervention effects -- 8. Medication interventions -- 9. Targeting hard to reach groups -- 10. Implementing behavior management strategies within a multi tiered model of prevention and intervention.
Includes bibliographical references (pages 147-160) and index.
Keywords: Behavior disorders in adolescence; Behavior disorders in children; Behavior therapy for children; Behavior therapy for teenagers